2012
DOI: 10.1016/j.jconrel.2012.04.042
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the imaging: Limitations of cellular uptake study in the evaluation of nanoparticles

Abstract: Poly(lactic-co-glycolic acid) (PLGA) nanoparticles (NPs) conjugated to a cell-penetrating peptide, TAT, was used to increase intracellular delivery of paclitaxel (PTX) to multi-drug resistant (MDR) cells. Efficient cellular uptake of the TAT-conjugated PLGA NPs was observed; however, it did not translate to increased killing of MDR cells. An investigation of drug release kinetics in phosphate-buffered saline containing Tween 80 led us to suspect that a significant fraction of the loaded PTX was released before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 49 publications
3
33
0
Order By: Relevance
“…A similar phenomenon was observed with PLGA NS modified with a cell-penetrating peptide, TAT (Gullotti and Yeo 2012). TAT was added to enhance cellular uptake of the NS, thereby facilitating drug delivery to multidrug resistant cells.…”
Section: Polymeric Nanospheres (Ns)supporting
confidence: 73%
See 1 more Smart Citation
“…A similar phenomenon was observed with PLGA NS modified with a cell-penetrating peptide, TAT (Gullotti and Yeo 2012). TAT was added to enhance cellular uptake of the NS, thereby facilitating drug delivery to multidrug resistant cells.…”
Section: Polymeric Nanospheres (Ns)supporting
confidence: 73%
“…For example, the previously mentioned PDLLA-MePEG micelles were expected to be stable, given the relatively low CMC and good colloidal stability lasting 24 h; however, they were dissociated in less than 1 h in blood (Burt et al 1999). We expected that PLGA NS would retain PTX well based on in vitro release kinetics study (Xu et al 2009) but found that the drug was released prematurely in the presence of amphiphilic components, cancelling potential advantages afforded by the carrier (Gullotti and Yeo 2012). The gaping difference between the estimated stability of NPs and their performance in biological systems is partly attributable to the lack of reliable methods to predict NP stability.…”
Section: Current Evaluation Methods Of Np Stabilitymentioning
confidence: 99%
“…This contributed an increase in hydrodynamic size and decrease in surface charge to -5 mV after the formation of PNA layer. Although the TAT layer increased the size, the surface charge was maintained to +29 mV creating cationic TPAPLGAHNPs, which made the penetration into the cell membrane easy [35,47]. The targeting moieties converted the PLGAHNPs to cationic polymeric NPs, which made them ideal carriers for gene delivery [47].…”
Section: Characterization Of Functionalized Npsmentioning
confidence: 99%
“…Although the TAT layer increased the size, the surface charge was maintained to +29 mV creating cationic TPAPLGAHNPs, which made the penetration into the cell membrane easy [35,47]. The targeting moieties converted the PLGAHNPs to cationic polymeric NPs, which made them ideal carriers for gene delivery [47]. Thus after the complete functionalization of PLGAHNPS, the cellular and nuclear uptake were studied in different cell lines.…”
Section: Characterization Of Functionalized Npsmentioning
confidence: 99%
“…[13][14][15] Despite its popularity as a drug carrier, PLGA does not readily interact with cells and thus requires surface modification to attain this ability. 16 However, PLGA functionalization is challenged due to the lack of surface reactivity and technical complexity. 17 Recent research has demonstrated that dopamine polymerization method has been widely exploited in functionalizing various types of substrates, such as polystyrene particles, 18 V 2 O 5 nanofibers, 19 SiO 2 and Fe 3 O 4 nanoparticles.…”
Section: Introductionmentioning
confidence: 99%